Comportamiento de soluciones nutritivas en forraje verde hidropónico usando semillas de maíz zea mays en invernadero - Ajila León, Neri Ernes (2008)
The present investigation that was carried out in the experimental farm Santa Inés of the Ability of Agricultural Sciences of the Technical University of Machala, located in the parish The Change. The area used for the rehearsal was of 5,04 m2, under covered with hothouse; the bookcase dedicated to the production of forage green hydroponics was built in wood with an extension of 4,20 m of long for 1,20 of wide and a height of 2,90 m; divided in three floors; the trays for the cultivation were also built wooden (1,0 x 0,5 m); the watering system was given by nebulización. The objectives of the investigation were: 1. to determine the behavior of the nutritious solutions during the process of development of the FVH; 2. to evaluate the economic yield of the biomass taken place by the FVH. Five more treatments were studied a witness, using a design completely randomizado, for the four first fertilizer was used to foliate (Stimufol 25-16-12) in dose of 20, 100, 200 and 500 g respectively; for T5 the formulation of the FAO, 250 solution ml was used A and 100 ml of the solution B; the witness one only worked with water. In the first variable, statistically it was determined that the height of plants to the 10 days, the average but high it corresponded to T3 and the but I go down the T6; and to the 14 days the averages of heights of plants but high you locates in the same order, first place T3 and the but low T6. The yield in weight was located in its order, T3, T1, T4, T5, T2 and T6. In the analyses proximales taking like base the content of proteins turns out to be better the T4. The relationship seed / forage average was of 1:4,8. By means of the economic analysis, the first crops usually are not profitable, but being projected to one year for the obtaining of numerous crops during the useful life of the infrastructure, it is profitable.